Changing of Sandy Soil Chemical Properties with Azolla microphylla and Quail Manure - Syamsiah, Jauhari; Herawati, Aktavia; Mujiyo, Mujiyo; Widijanto, Hery; Pangastuti, Triyana Suryaning; Putri, Elvia Febriani (JOURNAL OF TROPICAL SOILS, 2025)
Uncontrolled land conversion causes reduced land area for plant cultivation. The alternative used for rice cultivation is the marginal land such as sandy soil, however, several constraints led to very low productivity, so it needs proper management such as the addition of organic matter. The purpose of this study was to determine the changes in the chemical properties of sandy soil treated with Azolla microphylla and quail manure. The pot research was carried out in the Greenhouse of the Faculty of Agriculture, Universitas Sebelas Maret, with a factorial Completely Randomized Design (CRD) method, with 2 factors. Factor I was Azolla microphylla (A) (A0= 0, A1= 50, A2= 100, A3= 150 tons ha-1). Factor II was quail manure (Q) (Q0= 0, Q1= 20, Q2= 40 tons ha-1). Azolla microphylla and quail manure were incubated for 14 days under anaerobic conditions. The results showed that the application Azolla microphylla and quail manure increased chemical properties on sandy soil significantly. The addition of Azolla microphylla (100 tons ha-1) and quail manure (40 tons ha-1) increased the chemical properties of sandy soil such as cation exchange capacity (CEC), available-P, ammonium, available-K, available-Ca, electrical conductivity (EC) and redox potential (Eh).